Development of one-step isothermal methods to detect RNAs using hairpin-loop signal converters and proximity proteolysis reaction - Park, Hyeon Ji; Jung, Cheulhee; Yoo, Tae Hyeon (Biosensors and Bioelectronics, 2022)
Ribonucleic acids (RNAs) provide valuable information for biological systems and act as important indicators of disease states. RNAs are diverse in size and structure, and various strategies have been proposed for the detection of nucleic acids; however, developing them into point-of-care (POC) tests has been challenging as most of them consist of complex time-consuming steps. Here, we propose a strategy to assay RNAs using a hairpin-loop (HP) converter and proximity proteolysis reaction (PPR). Interaction between the loop part of HP and its target exposes a single strand of nucleotides, which acts as the template for PPR. A pair of protease and zymogen-conjugated nucleic acids associates with the adjacent regions of the template, resulting in an enhanced proteolysis reaction between protease and zymogen. The activated zymogen then generates a color signal through the hydrolysis of a chromogenic substrate. The combination of HP converter and PPR allowed the same pair of protease- and zymogen-nucleic acids to be used for different RNAs. Guidelines were provided for designing HP converters based on computational analyses and experimental characterizations. This strategy using an HP converter and PPR has been successfully applied to develop simple isothermal methods for the detection of various RNAs, including several microRNAs and KRAS mRNA, in the picomolar range in 1 h. The simplicity of designing HP converters and the beneficial properties of PPR as POC tests would enable the development of novel methods to detect RNAs under low-resource conditions.
Keywords: Chromogenic substrate; Color signals; Computational analysis; Disease state; Hairpin loop; Isothermal; Isothermal methods; Point of care; Proximity proteolysis reaction; Signal converters; Biosensing Techniques; MicroRNAs; Nucleic Acid Amplification Techniques; Nucleic Acids; Peptide Hydrolases; Proteolysis; Colorimetry; Hairpin loop; Isothermal; Proximity proteolysis reaction; RNA